Deciphering German diplomatic and naval attaché messages from 1900-1915. Issue 5 (3rd September 2021) - Lasry, George; Niebel, Ingo; Andersson, Torbjörn
Abstract: In World War One (WW I), the German diplomatic services and the Imperial Navy employed codebooks as the primary means for encoding confidential communications over telegraph and radio channels. The Entente cryptographic services were able to reconstruct most of those codebooks, to obtain copies of others, and to overcome various enhancements introduced by the Germans. A collection of diplomatic and naval attaché cryptograms from and to the German consulate in Genoa, dating from the late 19th Century to 1915, has been preserved and is held in German archives. 1 In this article, the authors describe the process of identifying the encoding methods, of reconstructing diplomatic codebooks, and of recovering the superencipherment applied to the German Navy's Verkehrsbuch. The vast majority of the messages can now be read in clear. The authors also provide the historical context for the messages, which shed new light on the impact of the mobilization and war declarations on the Genoa consulate, its role in gathering naval intelligence, and in assisting the Goeben and Breslau warships in their escape to the Dardanelles in August 1914. 2